Design of variable stiffness fixture for computerized embroidery machine based on shape memory polymer. (October 2022) - Yang, Yawen; Tian, Lei; Chen, Xi; Wang, Jiayuan; Zhang, Yongyan; Yin, Haibin
It is a challenge to handle the metal fixture used for cloth clamping in a computerized embroidery machine because of its fixed stiffness. Herein, a prototype that acts as a fixture to provide variable stiffness property is explored by discussing the potential of a thermal-sensitive epoxy resin-based shape memory polymer (SMP). The general model of fixture design is obtained after analyzing the working condition of the metal fixture. The structure of the SMP fixture is designed by discussing the material properties and working requirements of SMP, and a theoretical model is established to deduce the relationship between thickness and stiffness of the fixture. Six SMP fixtures that memorized clamping and opening state were manufactured with different proportions of raw materials. The results show that the designed fixtures have a lighter weight but higher clamping force than the metal fixture at room temperature (RT). It is the first work that demonstrates the potential of the SMP fixture to replace the metal fixture in the computerized embroidery machine and provides inspiration for product design with variable stiffness characteristic in engineering.